Postmenopausal hypertension: Role of the Renin Angiotensin System - Yanes, Licy L. (2010)
After menopause blood pressure (BP) increases in women. However, the underlying mechanisms responsible for postmenopausal hypertension are not completely understood. This study was conducted to determine the role that the renin angiotensin system plays in postmenopausal hypertension. Post estrous cycling (postmenopausal) spontaneously hypertensive rats or young female controls were treated with losartan, an angiotensin type 1 receptor blocker for 25 days. Mean arterial pressure was recorded continuously by radio-telemetry. Losartan significantly decreased blood pressure in postmenopausal rats and young female controls; but failed to normalize blood pressure in postmenopausal rats to levels found in young controls. Plasma renin activity and plasma angiotensinogen were significantly elevated and intrarenal angiotensin AT1 receptor and renin mRNA expression were significantly down-regulated in postmenopausal rats. Therefore, the renin angiotensin system only partially contributes to hypertension in postcycling spontaneously hypertensive rats, whereas hypertension in young females is mediated mainly by the renin-angiotensin system. The data suggest that other mechanisms besides activation of the renin angiotensin system are likely involved in postmenopausal hypertension.